Product Design Mall of Islamic Microfinance Institutions Supporting Economic Empowerment Islamic Boarding School Indonesia (Case Study Islamic Boarding School Abdussalam) - Alhifni, Anas; Huda, Nurul; Anshori, Muslich; Ahwarumi, Biyati (International Journal of Economics and Financial Issues, 2018)
Islamic Boarding School in Indonesia currently has many economic sectors including Islamic microfinance services such as Baitul Mal Wat Tamwil (BMT) one of Islamic Boarding School Abdussalam. The purpose of this study is to find out how the design of mall products that can be applied by Islamic microfinance institutions to support economic empowerment Islamic Boarding School. Research method in this research use qualitative approach with descriptive technique. Data collection techniques use observation, interview and focus group discussion to determine the right product design and in accordance with the condition of sharia micro finance institution in Islamic Boarding School. The results of this study indicate that the product design that can be developed by BMT Barokah Abdussalam is the design of cash waqf mall products with two approach models and Zakah infaq sadaqa mall product with two approach models, and from both models can be applied if BMT can optimize the source of social funds so that it can distribute the fund is one of them through the development of product design proposed in this research. The results of this study can be applied by other Islamic Boarding School who have sharia micro finance institutions and has the same criteria with Islamic Boarding School Abdussalam. Keywords: Product Design, Islamic Microfinance, Empowerment Islamic Boarding School JEL Classifications: I125, G23, DO2